Preserving Climacteric Fruits by Ripening Hormone Oxidation using nano-KMnO4 Confined within Nanoporous Carbon - Hernando, Addo; Ariyanto, Teguh; Prasetyo, Imam (ASEAN Journal of Chemical Engineering, 2019)
Climacteric fruits naturally can be over-ripened because of ripening hormone composed of ethylene gas. Removal of ethylene gas by potassium permanganate (KMnO4) has successfully preserved the fruit, but there is still a room for improvement through nano-confinement process. This study was conducted to compare the ethylene oxidation rate and fruit preservation ability of KMnO4 and nano-KMnO4. Ethylene oxidation experiment was conducted in a gas-tight vial filled with ethylene gas ( 20%v) and either KMnO4 or nano-KMnO4. Ethylene gas concentration inside the vial was periodically measured using gas chromatography (GC). The result revealed that ethylene oxidation rate by nano-KMnO4 is higher than KMnO4. The ethylene oxidation rate kinetic was modeled with a gas-solid reaction model, which is fundamentally more accurate than first-order reaction model. Fruit preservation experiment was conducted in sealed containers filled with banana (Musa acuminata) samples and either KMnO4 or nano- KMnO4, and stored at room temperature. The result revealed that banana preservation duration by nano-KMnO4 is remarkably longer than KMnO4, where unpreserved fruit was ripened after 7 days and fruit preserved by KMnO4 and nano-KMnO4 were ripened after 13 and 16 days respectively.